Feasibility Study of Bioretention Cells - Busenitz, Aubrey (Kansas State University. K-State Libraries., 2019)
This project is a formal report outlining the need for storm water mitigation in Manhattan, KS. I focus on bio retention cells, also known as rain gardens, as an effective solution to alleviate storm water runoff. For the purpose of this project, I am a hypothetical Project Engineer for the City of Manhattan reporting on a solution for the recent floods. Prior to this formal report, I wrote a proposal identifying the need for the research. I wrote the report to two main specific target audiences, expert engineers and business executives. I start the report by explaining the problems associated with the recent floods in Manhattan. My research analyzed the efficiency of bio retention cells to alleviate storm water runoff. I also reported the cost to design, construct, and maintain bio retention cells. I end my report with my final recommendations and conclusions for the City of Manhattan.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, grand prize
Keywords: bioretention cells; bio retention cells; flooding; storm water runoff; storm water mitigation; rain gardens